Preparação de óxidos mistos de níquel e zinco nanoparticulados a partir de combustíveis alternativos - Silva, Rayssa Rafaelli Nunes Melo da (2012)
The field of "Materials Chemistry" has been developing in recent years and there has been a great increase of interest in the synthesis and chemical and physical properties of new inorganic solids. New routes of synthesis and synthesis modified has been developed with the aim not only to optimize the processes in laboratory scale, but also on an industrial scale, and make them acceptable by current environmental legislation. The phenomenology of current solid state chemistry properties coupled with the high temperature superconductivity, ferromagnetism, porosity molecular and colors are evidence affected by the synthesis method, which in turn can influence the technological application of these materials. From this understanding, mixed oxides of nickel and zinc nanoparticulate were synthesized by microwave-assisted combustion route using three specific types of organic fuels employing the weight ratios 1:1/2 and 1:1 of cation metallic/fuel, in order to investigate the influence of such proportions to obtain the solids. The new fuels were chosen to replace, for example, urea or glycine that are the fuels most commonly preferred in this kind of synthesis. The powders without heat treatment were studied by Thermogravimetric analysis (TGA), X-Ray Diffraction (XRD) and then calcined at 900°C. After heat treatment, the samples were characterized by analysis of X Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The modified synthesis route porposed was effective for obtaining powders. Both the alternative fuels chosen as the different weight ratios employed, influenced in the morphology and obtaining oxides